2021
DOI: 10.4155/bio-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Absorptive Microsampling: Its Use in Covid-19 Research and Testing

Abstract: COVID-19 led to changes in the way blood samples are collected. As societies were isolated to control viral spread, access to facilities became limited. Remote sample collection with a volumetric microsampling approach, using Mitra® devices based on VAMS® technology, proved to be highly effective. It allowed people to collect high-quality samples at home and post them to a laboratory. This enabled scientists to conduct large serosurveillance studies, with results showing that seroprevalence of COVID-19 was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…[35][36][37] Biomarker analysis has primarily been assessed with serum or plasma, where all cellular mass including red blood cells, white blood cells, platelets are removed to reduce the complexity of the biofluid. 18 We found that the Mitra device (Neoteryx) which absorbs 10µl 38 when collected correctly through its volumetric absorptive microsampling (VAMS) technology, 39,40 facilitates self-administered blood collection from a finger lancet needle prick with highly reproducible replicate collection, 35,41 as demonstrated with very low coefficients of variation (%CV). The Mitra devices have been shown to be successfully utilized with many conventional diagnostic tests currently ordered by a physician and can be easily adapted for automation.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Biomarker analysis has primarily been assessed with serum or plasma, where all cellular mass including red blood cells, white blood cells, platelets are removed to reduce the complexity of the biofluid. 18 We found that the Mitra device (Neoteryx) which absorbs 10µl 38 when collected correctly through its volumetric absorptive microsampling (VAMS) technology, 39,40 facilitates self-administered blood collection from a finger lancet needle prick with highly reproducible replicate collection, 35,41 as demonstrated with very low coefficients of variation (%CV). The Mitra devices have been shown to be successfully utilized with many conventional diagnostic tests currently ordered by a physician and can be easily adapted for automation.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated that quantifying antibodies for the detection of COVID-19 from mail-in samples was possible. 43 Furthermore, we would direct the reader to a comprehensive manuscript detailing studies carried out using Mitra for COVID-19 published by Rudge et al 44…”
Section: Applications Covid-19mentioning
confidence: 99%
“…The collection of dried blood spots (DBSs), i.e., capillary blood from a finger, toe, or heel prick, has become a practical alternative to the collection of venous blood during the recent COVID-19 pandemic. , The pandemic has also underlined the major advantages of DBS sampling, which benefits from its minimal invasiveness, suitability for remote patient-centric blood sampling, and simple transport to a laboratory. The DBS sampling does not require trained personnel for blood draws not even the cold chain for the shipment; moreover, many analytes exhibit increased stability in dried samples .…”
Section: Introductionmentioning
confidence: 99%